2006
DOI: 10.1016/j.ymthe.2006.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Ranging Study of AAV-hAADC Therapy in Parkinsonian Monkeys

Abstract: The main medication for idiopathic Parkinson disease is L-Dopa. Drug efficacy declines steadily in part because the converting enzyme, aromatic L-amino acid decarboxylase (AADC), is lost concomitant with substantia nigra atrophy. Over the past decade, we have developed a gene therapy approach in which AADC activity is restored to the brain by infusion into the striatum of a recombinant adeno-associated virus carrying human AADC cDNA. We report here the results of an investigation of the relationship between ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 19 publications
5
63
0
Order By: Relevance
“…In light of findings from various in vitro preparations and rat models of PD (Azzouz et al, 2002;Bankiewicz et al, 2006a, b;Forsayeth et al, 2006;Jarraya et al, 2009), two gene therapy approaches to render striatal neurons as sources of dopamine or DOPA are currently being explored in clinical trials. In the first trial, the utility of a triple enzyme transfer is examined.…”
Section: Viral Vector-mediated Striatal Dopamine Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of findings from various in vitro preparations and rat models of PD (Azzouz et al, 2002;Bankiewicz et al, 2006a, b;Forsayeth et al, 2006;Jarraya et al, 2009), two gene therapy approaches to render striatal neurons as sources of dopamine or DOPA are currently being explored in clinical trials. In the first trial, the utility of a triple enzyme transfer is examined.…”
Section: Viral Vector-mediated Striatal Dopamine Replacementmentioning
confidence: 99%
“…In this case, active neurotransmitter production is expected only after the patients take LD, so that the magnitude of the functional effects could be adjusted by regulating the oral LD dose (Bjorklund et al, 2010b). Testing in MPTP-treated monkeys (Bankiewicz et al, 2006a, b;Forsayeth et al, 2006) showed stable long-term expression of the vector for up to 6 years, which was accompanied by improvement in clinical rating scores and a reduction of LD-associated side effects (Bankiewicz et al, 2006a, b;Forsayeth et al, 2006). A phase I clinical trial, started in 2005 in five patients who received bilateral intrastriatal vector administration, showed only modest efficacy in 'off' state 6 months post transfection.…”
Section: Viral Vector-mediated Striatal Dopamine Replacementmentioning
confidence: 99%
“…Animals slightly improved their parkinsonism after receiving AAV2-hAADC, because study animals were only mildly lesioned with MPTP in contrast to preclinical efficacy studies in which animals were severely overlesioned (Bankiewicz et al, 2006;Forsayeth et al, 2006). This high vector dose (7.0 · 10 11 VG) resulted in strong AADC expression in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…It was unnecessary to conduct an efficacy study of AAV2-hAADC in NHP because that has been abundantly established (Bankiewicz et al, 2006;Forsayeth et al, 2006;Hadaczek et al, 2010). These data form the basis of a proposed clinical trial of AAV2-hAADC in PD with the recognition that the delivery technique in previous phase I studies (Eberling et al, 2008;Christine et al, 2009;Muramatsu et al, 2010) was unable to ensure sufficient distribution and transgene expression to be able to achieve optimal non-rate-limiting AADC activity in transduced tissue .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation